The forgotten French: Exiles in the British Isles, 1940-44 - Atkin, Nicholas (Manchester University Press, 2003)
It is widely assumed that the French in the British Isles during the Second World War were fully-fledged supporters of General de Gaulle, and that across the channel at least, the French were a 'nation of resisters'. This highly provocative study reveals that most exiles were on British soil by chance rather than by design, and many were not sure whether to stay. Overlooked by historians, who have concentrated on the 'Free French' of de Gaulle, these were the 'Forgotten French': refugees swept off the beaches of Dunkirk; servicemen held in camps after the Franco-German armistice; Vichy consular officials left to cater for their compatriots; and a sizeable colonist community based mainly in London. Drawing on little-known archival sources, this study examines the hopes and fears of these communities who were bitterly divided among themselves, some being attracted to Pétain as much as to de Gaulle. It also looks at how they fitted into British life and how the British in turn responded. The author finds that while the public was often charitable, the Government was suspicious of their loyalties and even considered general internment. Illustrated throughout, this is essential reading for anyone interested in the British and French experiences of the Second World War